Labor Dystocia: A Common Approach to Diagnosis. (13th October 2015) - Neal, Jeremy L.; Lowe, Nancy K.; Schorn, Mavis N.; Holley, Sharon L.; Ryan, Sharon L.; Buxton, Margaret; Wilson‐Liverman, Angela M.
Abstract : Contemporary labor and birth population norms should be the basis for evaluating labor progression and determining slow progress that may benefit from intervention. The aim of this article is to present guidelines for a common, evidence‐based approach for determination of active labor onset and diagnosis of labor dystocia based on a synthesis of existing professional guidelines and relevant contemporary publications. A 3‐point approach for diagnosing active labor onset and classifying labor dystocia‐related labor aberrations into well‐defined, mutually exclusive categories that can be used clinically and validated by researchers is proposed. The approach comprises identification of 1) an objective point that strictly defines active labor onset (point of active labor determination); 2) an objective point that identifies when labor progress becomes atypical, beyond which interventions aimed at correcting labor dystocia may be justified (point of protraction diagnosis); and 3) an objective point that identifies when interventions aimed at correcting labor dystocia, if used, can first be determined to be unsuccessful, beyond which assisted vaginal or cesarean birth may be justified (earliest point of arrest diagnosis). Widespread adoption of a common approach for diagnosing labor dystocia will facilitate consistent evaluation of labor progress, improve communications between clinicians and laboring women, indicate when intervention aimed at speeding labor progress or facilitating birth may be appropriate, and allow for more efficient translation of safe and effective management strategies into clinical practice. Correct application of the diagnosis of labor dystocia may lead to a decrease in the rate of cesarean birth, decreased health care costs, and improved health of childbearing women and neonates.